Dual-Function Exocytosis Regulator Has Yet Another Job - Robinson, Richard (PLoS Biol, 2015)
A new study shows that synaptotagmins, known to regulate the fusion of neurotransmitter vesicles with synaptic membranes, are also needed for the prior tethering and priming of vesicles. Read the Research Article.